Effect of organic acid and natural antioxidant on the quality and shelf life of raw chicken meat at refrigerated storage - Islam, MR; Hasan, MM; Masum, MMR; Khan, M; Rahman, MM (Meat Research, 2025)
The present study was conducted to evaluate the shelf life and microbiological quality of raw chicken meat incorporated with organic acid and natural antioxidants at refrigerated storage (4±1ºC). The meat was stratified into four experimental groups: T0 (Control), T1 (1% Vinegar), T2 (1.5% Lemon Pulp), T3 (0.3% Tulsi leaf Extract). Assessments were systematically performed on days 0, 3 and 7 to determine a wide range of parameters including physicochemical characteristics oxidative stability, color value, Odor, microbial safety, and proximate composition. Throughout the storage period, organic acid and natural antioxidants-treated samples exhibited significantly reduced pH levels and higher water retention capacities (P<0.01) relative to the control. Throughout the storage period, comparatively lower viable count was detected in T1 treatment. Among them, 1% vinegar (T1) demonstrated superior oxidative stability, as evidenced by its significantly lower TBARS (P<0.01) values. The most preferable good odor was observed from T1 treatment and the lowest odor from T0 group. In different treatment groups color content significantly (P<0.05) decreased but in the control group color content decreased rapidly. From this comparative study it can be concluded that in case of sensory evaluation, 1% of vinegar is more appreciated and nutrient quality is more satisfactory.